Doing gender during the Covid-19 pandemic among academicians in Nueva Ecija, Philippines - Jed Airo L. Batino; Peachy G. Domingo; Ma. Edith N. Lim; Oliva B. Parico; Randolf Warren Gregorio T. Mayo II (Ho Chi Minh City Open University Journal of Science - Social Sciences)
Research on the division of labor within families needs to be conducted, particularly regarding how housework is divided, resisted, and modified, which is under-researched (Carlson et al., 2020). To address this gap, a survey was conducted to investigate the gender role attitudes and domestic division of labor of academicians from various colleges and universities in Nueva Ecija, Philippines. This survey included 43 male and 106 female respondents. Cross-tabulation, T-tests, and correlational analysis were employed to analyze the data. The T-test results revealed a positive gender role attitude among men and women. In terms of household involvement, on average, men spent approximately 25.42 hours per week on domestic responsibilities, whereas women dedicated 31.68 hours per week to these tasks. Interestingly, men allocate more time to household chores such as dishwashing and ironing clothes than women. This study enriches the ongoing conversation about how dual-earning couples manage their division of labor, particularly within academic settings. Furthermore, the correlation results indicate that men with higher income and higher educational attainment tended to endorse traditional gender role ideologies. In contrast, women with higher income and educational attainment were more likely to negotiate their domestic duties. These findings reveal that gender during the Covid-19 pandemic is nuanced by spouses’ relative income and educational attainment. Furthermore, those who embrace egalitarian attitudes tend to participate more in housework. Young children among dual-earning couples promote an egalitarian attitude where husbands assume childcare responsibilities, and couples are more inclined to engage in childcare activities jointly. The findings provide more profound insights by showcasing the potential for egalitarian attitudes within these couples. Additionally, the study highlights the pivotal role of young children in fostering such egalitarianism. Moreover, it observes that factors such as income and education can reinforce egalitarian values or contribute to dismantling traditional gendered divisions of labor within families.